Study of the Fluid Passing through the Screen in the Three Products Hydrocyclone Screen (TPHS): A Theoretical Analysis and Numerical Simulation - Haizeng Liu (Processes, 2022)
The three products hydrocyclone screen (TPHS), a branch of the hydrocyclone, effectively removes the fish-hook effect, which has been used in the industrial field. The current cylindrical screen in the TPHS generates the characteristic flow known as the screen underflow, which has a significant impact on device performance. To investigate the flow behaviour of the fluid passing through the screen, a combination of a dynamic analysis and a numerical simulation was used. The permeating process in the TPHS was abstracted by a simple fan mode in this work to generate the flow-rate equations and the driving-force models. The pressure difference was the driving force for the screen penetration in the ideal fluid, but it also included a viscous force in the viscous fluid. Furthermore, at the same inlet velocity, the viscous fluid had a higher flow rate than the ideal, indicating that the viscosity promoted the fluid penetration. Meanwhile, as the inlet velocity increased, the mass flow of the screen backflow increased, while the corresponding proportion first rose to a peak then dropped and then gradually stabilised. Furthermore, a flow equation for the screen underflow in the TPHS was developed, which is related to the structural parameters (the rotation radius, the length of the cylindrical screen, the aperture size, and the open-area percentage) and the process parameters (the dynamic viscosity of the fluid and the pressure difference between the feed inlet and the screen outlet).